Inclusion Complexes of Rifampicin with Native and Derivatized Cyclodextrins: In Silico Modeling, Formulation, and Characterization - Qonita Kurnia Anjani; Juan Domínguez-Robles; Emilia Utomo; María Font; María Cristina Martínez-Ohárriz; Andi Dian Permana; Álvaro Cárcamo-Martínez; Eneko Larrañeta; Ryan F. Donnelly (MDPI AG, 2021)
Inclusion complexation of rifampicin (RIF) with several types of cyclodextrins (βCD, hydroxypropyl-βCD, γCD, hydroxypropyl-γCD) in aqueous solutions at different pH values was investigated to assess the interactions between RIF and cyclodextrins (CDs). Molecular modeling was performed to determine the possible interactions between RIF and CDs at several pH values. The inclusion complexes were characterized by differential scanning calorimetry, Fourier transform infrared spectroscopy, powder X-ray diffractometry, and scanning electron microscopy. Moreover, this study evaluated the dissolution profile and antibacterial activity of the formed complexes. Phase solubility analysis suggested the formation of RIF-CD affirmed 1:1 stoichiometry at all pH values (except RIF-βCD at pH 4.0 and both βCD and γCD at pH 9.0). The inclusion complexation of RIF with CD successfully increased the percentage of RIF released in in vitro studies. The inclusion complexes of RIF exhibited more than 60% of RIF released in 2 h which was significantly higher (p < 0.05) than release of pure RIF, which was only less than 10%. Antibacterial activity of RIF-CD complexes (measured by the minimum inhibitory concentration of RIF against Staphylococcus aureus and methicillin-resistant Staphylococcus aureus) was lower for both RIF-βCD and RIF-HPγCD at pH 7.0 to pure RIF suspension. In conclusion, this work reports that both βCD and γCD can be used to enhance the solubility of RIF and thus, improve the effectivity of RIF by decreasing the required daily dose of RIF for the treatment of bacterial infections.